Sense of community participation in tourism development: a case in Cox’s Bazar, Bangladesh / Hazmal Ismail ... [et al.] - Ismail, Hazmal; Alam, Md Mahbub; Md Zain, Nur Adilah; Wan Salman, Wan Ahmad Nasroun; Hanafiah, Mohd Hafiz (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
This study delves into the relationship between the sense of community and participation in tourism development, focusing on the dimensions of membership, influence, integration, and the fulfillment of needs, along with shared emotional connection. Specifically conducted in Cox's Bazar, Bangladesh, this research employs a quantitative method and a deductive approach, forming hypotheses based on the theory of the sense of community. To collect data, a 5-point Likert Scale self-administered questionnaire was distributed physically. A total of 384 samples were gathered, representing the broader population of 2,823,265 local members in Cox's Bazar, Bangladesh. The findings of this study indicate that each dimension of the sense of community - membership, integration and fulfillment of needs, influence, and shared emotional connection - significantly influences community participation in the context of Cox's Bazar, Bangladesh. These insights are valuable not only for academics and researchers but also for policymakers and stakeholders in the tourism industry, offering a deeper understanding of how the sense of community can drive and enhance participation in tourism development. This research contributes to the growing body of knowledge on tourism and community engagement and has the potential to inform strategies for sustainable tourism development in the region.